Transforming Language Learning: Project-Based Learning through Video Conferencing Platforms as Tools to Enhance Willingness to Communicate - Panggabean, Hanna Maria; Safi’i, Muhamad; Elviani, Mutia; Manik, Ronika Apriyanti; Liani, Ghustiva (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examined the effectiveness of project-based learning (PBL) that was integrated with video conferencing platforms such as OmeTV to assess its impact on willingness to communicate (WTC) in English. Fifty students from vocational college were selected as an experimental group who received PBL approach, and another fifty students participated as a control group, who only attended video conferencing session. The study employed mixed methods, incorporating both quantitative and qualitative data, to investigate students’ improvement on WTC before and after the implementation of PBL activities. A questionnaire was developed by adopting WTC model from McIntyre (1998) to assess the effectiveness of PBL on the students’ WTC; meanwhile, in-depth interviews took place to explore the experiences and perspectives of how a supportive English environment can influence their WTC, challenge them to use English more actively and interactively, and overcome the difficulty of misunderstanding across cultures. The findings revealed a significant improvement in WTC for the experimental group, indicated by a t-value of 16.780 (p 0.001) and an R² increase from 45.3% to 85.4%. Conversely, the control group showed moderate improvement (t-value of 12.333, p 0.001) and an R² increase from 12.8% to 76%. This implied that video conferencing alone had a positive effect on the students’ WTC, but it was less impactful compared to the experimental groups who received PBL approach. Meanwhile, the interview results highlighted three key themes, namely, 1) feeling motivated to continue communicating in English and building confidence as an indicator of improved WTC, 2) challenges with foreigners helped them identify and overcome their language barrier and fear of making mistakes, and 3) usefulness of video conferencing session that provided authentic communication. Video conferencing platforms, such as OmeTV, enhance students' communication skills and build their confidence. Overall, the study contributes to the development of pedagogical approaches, as PBL offered student-centered learning to enhance their English language proficiency and communicative competence in the context of vocational students.